Falsely prolonged activated partial thromboplastin time : a pre- and post-analytical issue - Gils, Charlotte (Array, 2018)
This case highlights two common pre-analytical problems identified in routine coagulation testing of activated partial thromboplastin time (aPTT),which were overlooked because of a concurrent flag code indicating no coagulation and the result was replaced by asterisks. It concerns a boy withgastrointestinal bleeding and prolonged aPTT >300 seconds, which raised the suspicion of haemophilia. When all other coagulation parameters(including specific coagulation factors VIII and IX) turned out to be normal, aPTT was re-measured using another analysis principle, which revealeda normal aPTT. The primary aPTT result turned out to be aborted due to concurrent haemolysis and lipaemia, but was erroneously interpreted asprolonged coagulation. The lesson is awareness of the possibility of numerous flag codes on the same sample overruling each other, and awarenesson the responsibility in the post-analytical phase that must be carried by increased educational focus and by the manufacturers.